EFEKTIVITAS KONSELING BEHAVIORAL MODEL KRUMBOLTZ UNTUK MENGEMBANGKAN KEPUTUSAN KARIR SISWA - Suhardita, Kadek; Sapta, I Ketut; Yuliastini, Ni Komang Sri; Sastrawati, Wayan Udayani; Purwanti, Ni Kadek Chandra (Widyadari: Jurnal Pendidikan, 2019)
This research is an experimental study to cultivate student learning outcomes of grade X SMA Negeri 1 Busungbiu. Conditioning and user behavior are limited to those that can be used purely, can not be handled strictly. In this study, the control variables are Krumbotz counseling behavior, while the control class in this study is not given with the same as the experimental class. The sample of research, determined by random sampling technique is random sampling technique through drawing. Based on the First Hypothesis Testing the thitung value of -10.632 with df = (N-1) = (35-1) = 34 and 5% significance level then obtained the value of ttable of 2.032. Since it is larger than ttable, this proves that the first hypothesis in this study can be used and the behavior behavior of the Krumboltz counselor is effective for making decisions for grade X students of SMA Negeri 1 Busungbiu. Based on Second Hypothesis Testing The average tcount of 8,739 with df = (N1-1) + (N2-1) = (35-1) + (35-1) = 68 and 5% significance level hence the obtained ttable value of 2.011. Since it is larger than ttable, it proves that there are two factors in this study that can be used to determine the behavior of the Krumbolt behavior model (experimental group) with groups of students who are not Based on these results it will be done counseling behavior Krumboltz behavioral model to develop decisions that can be categorized well and can provide a very effective contribution